Methods for using neural networks in new media classes - Serdali, Б. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2026)
This study aims to identify the possibilities of using neural networks (hereinafter referred to as neural nets) as an innovative method for creating an interactive educational environment in disciplines taught within the educational programs in the field of "Journalism and Reporting." The article comprehensively examines modern methods of applying neural nets in the process of teaching new media. In particular, attention is paid to the role of neural nets in developing educational content and personalizing the learning process, as well as the opportunities to enhance interaction between the teacher and the student. During the study, by rethinking the traditional lesson structures in journalism faculties, practical approaches to constructing the technological framework of lessons based on the use of neural nets are proposed. These approaches are aimed at developing students’ digital literacy and creative abilities. The scientific novelty of the research lies in the initial formulation of methodological recommendations for designing the technological structure of lessons oriented toward achieving educational goals through the integration of neural nets into the new media learning process. These recommendations are intended to update the content of education in journalism and to enhance the professional competence of future specialists. The research results demonstrated the significant potential of neural nets in the educational process. They are considered as an auxiliary tool for the teacher, as well as an effective digital resource for developing students’ communicative competence and improving "soft skills" such as creativity, critical thinking, and teamwork.